Effects of juvenile hormone mimics on larval development and metamorphosis of Drosophila melanogaster. - Riddiford, L.M.; Ashburner, M. (General and Comparative Endocrinology, 1991)
To determine if prolonged larval exposure to juvenile hormone (JH) could influence the decision to metamorphose, Drosophila melanogaster larvae were reared from hatching on medium containing either of the JH mimics, methoprene or 2-[1-methyl-2-(4-phenoxyphenoxy)-ethoxy]-pyridine (S31183). The latter was 23 times more active as a JH mimic in the white puparial assay (ED50 = 0.22 pmole). Larval development and pupariation were unaffected except at 1000 ppm methoprene and 10 ppm or higher S31183 where larval life was prolonged with increased mortality in the second instar. Adult eclosion was prevented by concentrations greater than 1 ppm methoprene and 0.1 ppm S31183. At low concentrations only adult abdominal development was affected, but at the higher concentrations an increasing percentage was blocked at the pupal stage. This latter effect was considerably diminished when the treatment was begun in the mid second instar. The methoprene-resistant mutations, Met1 and Met2, were 10 and 6 times more resistant to S31183 in the white puparial assay and about 20 times more resistant in the larval feeding experiments than the wild-type, indicating that the effects seen are typical of JH. These studies suggest that excess JH may affect adult development of imaginal structures if present at the onset of postembryonic cell proliferation of the imaginal discs or histoblasts. Thus, commitment for adult differentiation must occur early during this proliferative phase.